2011
DOI: 10.1080/02786826.2011.587477
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Measurements of Amplification of the Absorption Cross Section for Coated Soot Aerosols

Abstract: A quantitative understanding of the absorption and scattering properties of mixed soot and aerosol particles is necessary for evaluating the Earth's energy balance. Uncertainty in the net radiative forcing of atmospheric aerosols is relatively large and may be limited by oversimplified models that fail to predict these properties for bare and externally mixed soot particles. In this laboratory study of flame-generated soot, we combine photoacoustic spectroscopy, particle counting techniques, and differential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 49 publications
5
58
2
Order By: Relevance
“…During the initial morphology change, a thin dielectric coating layer hinders the interaction of electromagnetic (EM) coupling between neighboring spherules, and the internal spherules are shielded by the outer ones, likely responsible for little absorption enhancement (8,24). For fully compact BC particles, efficient EM coupling between neighboring spherules contributes to an enhanced MAC, in addition to the lensing effect (15,24). The Mie theory with the core−shell assumption for homogeneous spherical particles (25,26) is used to calculate MAC.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…During the initial morphology change, a thin dielectric coating layer hinders the interaction of electromagnetic (EM) coupling between neighboring spherules, and the internal spherules are shielded by the outer ones, likely responsible for little absorption enhancement (8,24). For fully compact BC particles, efficient EM coupling between neighboring spherules contributes to an enhanced MAC, in addition to the lensing effect (15,24). The Mie theory with the core−shell assumption for homogeneous spherical particles (25,26) is used to calculate MAC.…”
Section: Significancementioning
confidence: 99%
“…As a key short-lived climate forcer, the magnitude of BC direct radiative forcing (DRF) is dependent on the mixing state, i.e., whether particles are externally or internally mixed with other aerosol types (5,6), and atmospheric aging by coating with secondary aerosol constituents (such as organics and sulfate) enhances the mass absorption cross-section (MAC) (5)(6)(7)(8)(9). Previous laboratory studies conducted under controlled experimental conditions yielded a broad range of MAC enhancements from 1.05 to 3.50, varying with the diameter, morphology, and coating of BC particles (7)(8)(9)(10)(11)(12)(13)(14)(15). On the other hand, a field measurement indicated a negligible absorption enhancement of ambient BC particles under a variable mixing state (16).…”
mentioning
confidence: 99%
“…Although a core-shell model can be used to estimate this AE value, it relies on the challenging estimation of the relative location and thickness of the shell at various conditions. Laboratory studies show that the AE changes very little when the shell is thick enough (Bueno et al, 2011;Cross et al, 2010;Shiraiwa et al, 2010;Shamjad et al, 2012;Knox et al, 2009), all estimating a maximum AE value around 2. Bond et al (2006) conducted a series of core-shell calculations and found that the AE is 1.9 for thickly coated BC.…”
Section: Updated Bc Properties For Optical Calculationmentioning
confidence: 99%
“…Despite that, the core-shell configuration cannot always represent the absorption variability in the laboratory and field observations (Adachi et al, 2010;Bueno et al, 2011;Cappa et al, 2012b, a). The latter might be due to the miss-representation of the BC particle aggregation and mixing, as shown by more detailed light scattering modeling studies performed by Kahnert (2010b), Scarnato et al (2013) and .…”
Section: B V Scarnato Et Al: Optical Properties Internally Mixed Mmentioning
confidence: 99%
“…The latter might be due to the miss-representation of the BC particle aggregation and mixing, as shown by more detailed light scattering modeling studies performed by Kahnert (2010b), Scarnato et al (2013) and . Recent studies show that internal mixing of BC with other aerosol materials in the atmosphere can alter its aggregate shape (Zhang et al, 2008;Xue et al, 2009;Cross et al, 2010;China et al, 2013), absorption of solar radiation (Bueno et al, 2011;Cappa et al, 2012b), and radiative forcing (Adachi et al, 2010;Kahnert et al, 2012). China et al (2014), furthermore, characterized the predominant mixing and morphology types observed with the electron microscopes from samples collected in different locations and for different sources (i.e., biomass burning aerosol and vehicle exhaust) by classifying BC into four main classes (bare BC, inclusions, thinly coated and embedded BC); similar classes where identified by Scarnato et al (2013) for laboratory-generated mixtures of BC and sodium chloride (an aerosol mixture resembling dirty marine aerosol).…”
Section: B V Scarnato Et Al: Optical Properties Internally Mixed Mmentioning
confidence: 99%